Interleukin-6 as a biomarker of sepsis and its clinical utility in predicting mortality: a prospective observational study - Ameen, Syed S; Hegde, Shreya; Parida, Amrita; Kateel, Ramya; V, Manju (The Journal of Infection in Developing Countries, 2025)
Introduction: Majority of patients admitted to intensive care units (ICUs) succumb to sepsis and its complications. However, currently available predictors fail to reliably gauge the severity of organ damage. There is a pressing need to identify biomarkers that can accurately forecast outcomes. Interleukin-6 (IL-6) has emerged as a potential biomarker, with some studies suggesting its utility as an early predictor of multi-organ failure in sepsis. This study evaluated the role of IL-6 in predicting mortality in an Indian ICU setting. Methodology: This prospective observational study included adult patients diagnosed with sepsis and a quick SOFA score ≥ 2. IL-6 levels, SOFA scores, and other clinical parameters were measured within 24 hours of admission. Univariate and multivariate analyses identified factors associated with mortality. Results: The overall ICU mortality rate was 39%. Multivariate analyses indicated that IL-6 levels, total SOFA scores, and number of antibiotics used were independently associated with mortality. The IL-6 levels showed strong positive correlations with the total SOFA score (r = 0.77, p < 0.001) and individual organ dysfunction scores; particularly in cardiovascular (r = 0.61, p < 0.001), renal (r = 0.64, p < 0.001), and central nervous system (r = 0.6, p < 0.001). Conclusions: IL-6 levels, in combination with SOFA scores, provide a robust predictor of mortality in sepsis patients. The strong correlation between IL-6 levels and organ dysfunction scores suggests its potential as a biomarker for sepsis severity and progression.